Niemcy w Królestwie Polskim wobec odrodzenia państwa polskiego w 1918 r. - Woźniak, Krzysztof Paweł (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2011)
Prior to the First World War there were approximately 500 thousand German people living in the Kingdom of Poland, 75% of them living in the countryside. The majority of them perceived the national consciousness only in a sense of the common language and religion (confession). „The late awakening” of national consciousness was as a result of the war events. The large number of Germans gained wait-and-see attitude towards the political outcomes of the war. The most initiative branch of the Germans were so called ‘aktivists’. They felt responsible for the whole German community in the Kingdom of Poland. They constituted ‘Deutsches Verband’, which soon consisted of 20 thousand members, ‘Deutsch-evangelischen Landesschulverband’, ‘Deutschen Genossenschaftsverband’. The complete loyalty towards to the forming Polish state was publicly declared. Germans’ only claim regarded the right to use German language ‘at home, at school and in the church’. The forcing attempt of making the Evangelical-Augsburg Church a national church failed.